THE IMPORTANCE OF EXPLAINABILITY IN MEDICAL AI AND PREDICTOR REDUCTION IN CARDIOVASCULAR RISK ASSESSMENT (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article discusses the critical importance of explainability in medical AI, particularly in the context of cardiovascular risk prediction. It highlights the necessity of transparent AI systems for clinician trust, patient-centered care, regulatory compliance, and bias detection. The role of predictor reduction using XAI methodologies, such as SHAP and LIME, is emphasized as a means to enhance model efficiency and interpretability. The article also explores the challenges of achieving explainability, the evolving landscape of XAI research, and the future prospects of integrating explainable models with real-world healthcare systems. Ultimately, it underscores the need for interdisciplinary collaboration to ensure AI-driven medical decision-making is both effective and ethically sound.
Keywords: Explainable AI (XAI); Medical AI; Predictor Reduction; Cardiovascular Risk Assessment; Myocardial Infarction; Adverse Cardiovascular Events; SHAP (Shapley Additive Explanations); LIME (Local Interpretable Model-agnostic Explanations)